A Biodiversity Observation Network to support conservation action and mainstream knowledge in Canada - Andrew Gonzalez; Mary I. O'Connor; Amanda E. Bates; Kyle Bobiwash; A. Cole Burton; Paul van Dam-Bates; Isaac Eckert; Dominique Gravel; C. Julián Idrobo; Laura Pollock; Andrew D.F. Simon; Margaret A. Slein; et al. (FACETS)
Canada has begun an ambitious project to build an observing system to monitor the changing state of its biodiversity and ecosystems. A Canada-wide Biodiversity Observation Network (CAN BON) can support the measurement, mapping, and modelling of biodiversity change—the losses and gains in the diversity of plant, animal, and microbial life—and ecosystem services. This initiative responds to eight challenges presently constraining Canada's capacity to deliver timely and robust knowledge to achieve its biodiversity goals. CAN BON is conceived as a network connecting diverse organizations to support sustained biodiversity monitoring by collaboration among universities, museums, governments, industries, NGOs, community groups, and Indigenous organizations. This inclusive network will “mobilize monitoring data” to (1) combine observation and computing infrastructures and traditional knowledge to track and understand biodiversity losses and gains across the country; and (2) link the accumulated data and knowledge to models to inform the detection and attribution of biodiversity change needed to support biodiversity policy with forecasts from local to national levels. We expect that CAN BON will foster the mainstreaming of biodiversity data and knowledge into other sectors of the economy and society, and thereby support the technical and social innovation in Canada's transition to a nature-positive future.